Mental Health dalam Perspektif Akidah Islam: Peran Sabar, Syukur dan Ihktiar dalam Mengatasi Kecemasan - Najamudin Najamudin; Dwi Muliati; Anisa Anisa; Andika Mulyansyah; Nur Indah Tiana (Jurnal Manajemen dan Pendidikan Agama Islam, 2026)
Mental health is an essential aspect of human life that is deeply connected to one’s spiritual and faith condition. In the Islamic creed (ʿaqīdah) perspective, mental well-being is not merely defined by emotional stability or positive thinking but by one’s ability to maintain faith, surrender to Allah, and face life’s trials with patience and gratitude. Islam teaches that the source of inner peace (ṭuma’ninah) lies in closeness to Allah through remembrance (dhikr), prayer, and belief in divine destiny (qadha and qadar). Hence, a strong foundation of faith is crucial in maintaining a balanced psychological state for Muslims. In addition to patience and gratitude, the concept of ikhtiar (effort) also plays a vital role in overcoming anxiety. A Muslim is taught to make sincere efforts while trusting in Allah’s will, thereby achieving harmony between physical endeavor and spiritual strength. By internalizing the values of patience, gratitude, and effort, individuals can develop strong mental resilience, manage stress wisely, and find meaningful purpose in life’s challenges. This study highlights the significant role of Islamic teachings in fostering holistic mental health rooted in spiritual tranquility.